2015
DOI: 10.1155/2015/868707
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Lung Ultrasonography for the Detection of Community-Acquired Pneumonia: A Pilot Study

Abstract: Background and Objective. Chest X-ray is recommended for routine use in patients with suspected pneumonia, but its use in emergency settings is limited. In this study, the diagnostic performance of a new method for quantitative analysis of lung ultrasonography was compared with bedside chest X-ray and visual lung ultrasonography for detection of community-acquired pneumonia, using thoracic computed tomography as a gold standard. Methods. Thirty-two spontaneously breathing patients with suspected community-acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 38 publications
0
41
1
6
Order By: Relevance
“…In contrast to our study, Francesco et al (17) found that the sensitivity of LUS in identifying parenchymal consolidation was much lower than previously reported (59 versus 88-95%) (21,26,27). In a previous study of critically ill patients (28), LUS had a high accuracy in detecting consolidations due to different causes, which was explained by the fact that most of these reached the pleura.…”
Section: Diagnosis Of Pneumonia In Adultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our study, Francesco et al (17) found that the sensitivity of LUS in identifying parenchymal consolidation was much lower than previously reported (59 versus 88-95%) (21,26,27). In a previous study of critically ill patients (28), LUS had a high accuracy in detecting consolidations due to different causes, which was explained by the fact that most of these reached the pleura.…”
Section: Diagnosis Of Pneumonia In Adultscontrasting
confidence: 99%
“…In a previous recent study (16), quantitative lung ultrasonography (QLUS) proved to be an accurate method to evaluate extravascular lung water in a model of pulmonary edema. It can be hypothesized that QLUS may also be useful for detection of pulmonary consolidations of different origins (17).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the false negative results usually occurred when the consolidation was located far away from pleura and hided deep in the lung parenchyma. In addition, quantitative LUS (QLUS) was evident to be an impressive approach of pneumonia detection, showing a higher sensitivity and specificity than regular LUS (23). The combination of LUS and microbiological gram stain caused a conclusive increase in the likelihood of pneumonia diagnosis (26).…”
Section: Discussionmentioning
confidence: 99%
“…Among all 14 studies, 11 were carried out in emergency department (ED) or medical wards (10,(15)(16)(17)(18)(19)(20)(22)(23)(24)(25), and 3 were conducted in intensive care unit (ICU) (14,21,26). Hemithorax was used as the study unit for result interpretation in one study (23), while others counted by patient.…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation